Examining the role of fan support on home advantage and home win percentage in professional women`s basketball - Alonso-Pérez-Chao, E.; Martín-Castellanos, A.; Nieto-Acevedo, R.; Lopez-García, A.; Portes, R.; Gómez, M. Á. (Perceptual and Motor Skills, 2024)
Our main aim in this study was to analyze any differences in Win Percentages at Home (HW) that might represent a Home-Court Advantage (HA) in women`s professional basketball. A secondary objective was to analyze how team ability might modify the HA effect by comparing any interaction effect between HW and team ability in games played with and without fans. We collected data from first Spanish female basketball divisions, using a linear mixed model (LMM) for repeated measures to identify differences between time periods (games with fans vs. games without fans) for HA and HW. When comparing games with and without fans, we found no significant HA and HW differences (p = .283 and p = .872, respectively). In fact, interestingly, we observed higher win values when fans were absent. Additionally, during the COVID-19 shut down stage, HA increased; but it returned to pre-pandemic levels afterward, with no significant differences between these periods (p = .482). Similarly, while HW seemed to increase during the COVID-19 shut down period and continued improving in the post-pandemic phase, there were actually no statistically significant differences (p = .772). Higher HA and HW were evident without fans during the pandemic compared to the pre-pandemic period when fans were present in women`s professional basketball. During the post-pandemic period, HA decreased upon fans` return, while HW continued increasing. We discuss possible bases for these unexpected findings.